Intensity-modulated radiotherapy for cushing’s disease: single-center experience in 70 patients - Lian, Xin; Xu, Zhuoran; Sun, Shuai; Wang, Weiping; Zhu, Huijuan; Lu, Lin; Hou, Xiaorong; Zhang, Fuquan (Frontiers in Endocrinology, 2023)
Context: Intensity-modulated radiotherapy (IMRT) is a modern precision radiotherapy technique for the treatment of the pituitary adenoma.Objective: Aim to investigate the efficacy and toxicity of IMRT in treating Cushing's Disease (CD).Methods: 70 of 115 patients with CD treated with IMRT at our institute from April 2012 to August 2021 were included in the study. The radiation doses were usually 45-50 Gy in 25 fractions. After IMRT, endocrine evaluations were performed every 6 months and magnetic resonance imaging (MRI) annually. Endocrine remission was defined as suppression of 1 mg dexamethasone test (DST) or normal 24-hour urinary free cortisol level (24hUFC). The outcome of endocrine remission, endocrine recurrence, tumor control and complications were retrieved from medical record.Results: At a median follow-up time of 36.8 months, the endocrine remission rate at 1, 2, 3 and 5 years were 28.5%, 50.2%, 62.5% and 74.0%, respectively. The median time to remission was 24 months (95%CI: 14.0-34.0). Endocrine recurrence was found in 5 patients (13.5%) till the last follow-up. The recurrence-free rate at 1, 2, 3 and 5 years after endocrine remission was 98.2%, 93.9%, 88.7% and 88.7%, respectively. The tumor control rate was 98%. The overall incidence of new onset hypopituitarism was 22.9%, with hypothyroidism serving as the most common individual axis deficiency. Univariate analysis indicated that only higher Ki-67 index (P=0.044) was significant favorable factors for endocrine remission.IMRT was a highly effective second-line therapy with low side effect profile for CD patients. Endocrine remission, tumor control and recurrence rates were comparable to previous reports on FRT and SRS.